Evaluación de los cambios en las propiedades de los fluidos de perforación a diferentes inclinaciones de la celda de rolado durante una simulación con la prueba SAG (2023)
In this study, conducted at Ecopetrol's Mud Laboratory of the Innovation and Technology Center, an analysis was carried out on the effects caused in the drilling fluid after undergoing static aging with different incline angles. Subsequently, the rheological properties and barite settling at different incline angles were evaluated. The OBM fluid was subjected to pressure and temperature conditions for 16 hours following the standard API laboratory procedures. Duplicate tests were conducted to ensure the repeatability of the experiments, and the results showed no significant variations, maintaining consistent working conditions and ensuring result reliability. The findings indicate that after subjecting the drilling fluid to static aging, its rate/velocity properties have the potential to affect solid settling. Additionally, efficient barite settling was observed at all evaluated angles, with dimensionless values of 0.535, 0.527, and 0.530 (dimensionless values) for 45°, 60°, and 90° angles, respectively. The calculated factor falls within the SAG factor range, 0.500 < SAG < 0.530, representing characteristic behavior of barite particle settling in the mud. However, the 60° angle exhibited greater efficiency in particle suspension. Further evaluation of the fluid's rheological characterization after the SAG test provided relevant information about its behavior under simulated working conditions. The results, backed by duplicate tests conducted in a renowned laboratory, are essential for optimizing drilling operations and ensuring good well control. It is recommended to consider implementing fluid rolling in future operations and evaluate other incline angles and fluid compositions to gain a better understanding of fluid behavior in different scenarios. In conclusion, this study provides solid evidence of the benefits of fluid rolling concerning rheological properties and barite settling. It also emphasizes the importance of test repeatability and evaluation of fluid rheological characterization after the SAG test. These findings contribute to the continuous improvement of drilling operations and well control optimization.